THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE ON ORGANIZATIONAL PERFORMANCE WITH EMOTIONAL INTELLIGENCE AS A MEDIATION VARIABLES: A CASE STUDY AT THE JATIMELATI BEKASI VILLAGE OFFICE - Victorystar Mona; Suharto; Iwan Kurniawan Subagja (International Journal of Business and Social Science Research, 2020)
This study aims to examine the influence of transformational leadership style and organizational culture on organizational performance with emotional intelligence as a mediation variable. This research uses an explanatory research approach. Explanatory research is meant to explain the causal relationship between variables through hypothesis testing or the goal of obtaining appropriate testing in drawing causal conclusions between variables and then selecting alternative actions. The basic reason for using explanatory research is because the purpose of this study is to explain and examine the effect of transformational leadership, organizational culture and emotional intelligence on organizational performance at the Jatimelati Village Office, Bekasi. The population in this study were all sub-district office employees, amounting to 30 people. In this study, in determining the sample using saturated samples. Researchers set the sample in this study consisting of 30 employees. Based on result that partially, it shows that there is a positive and significant influence between transformational leadership style variables on emotional intelligence. Partially, it shows that there is a positive and significant influence between organizational culture variables on emotional intelligence. Partially, it shows that there is a positive and significant influence between transformational leadership style variables on organizational performance variables. Partially it shows a positive and significant influence between organizational culture variables on organizational performance variables. The emotional intelligence variable does not influence organizational performance this is in contrast to previous research. So that it distinguishes this research from previous research. The results showed that simultaneously there was an influence between transformational leadership style and organizational culture on organizational performance, with emotional intelligence as an intervening variable